Excessive generalisation of conditioned fear in trait anxious individuals under ambiguity. (August 2018) - Wong, Alex H.K.; Lovibond, Peter F.
Abstract: Trait anxiety has been widely accepted as a vulnerability factor for the development of anxiety disorders. However, few studies have examined how trait anxiety may affect fear generalisation, which is believed to be a core feature of anxiety disorders. Using a single-cue conditioning paradigm, the current study found a range of discrete generalisation gradients in both expectancy ratings and skin conductance, which were highly consistent with participants' reported abstract rules. Trait anxious participants showed the same level of threat expectancy to the conditioned cue as low anxious participants. However they showed over-generalisation to novel test stimuli, but only when they failed to identify a clear rule. This result suggests that over-generalisation of fear may be a special case of the more general principle that trait anxiety is associated with excessive threat appraisal under conditions of ambiguity. Highlights: Fear generalisation in high and low anxious individuals was tested in a single-cue conditioning paradigm. Participants reported a range of generalisation rules such as linear and similarity-based. Generalisation gradients were highly consistent with the inferred rules. High anxious individuals showed over-generalisation of fear, but only when they failed to identify any clear rules.